Exploring landowners' perceptions, motivations and needs for voluntary conservation in a cultural landscape. Issue 3 (17th July 2020) - Cortés‐Capano, Gonzalo; Toivonen, Tuuli; Soutullo, Alvaro; Fernández, Andrés; Dimitriadis, Caterina; Garibotto‐Carton, Gustavo; Di Minin, Enrico
Abstract: While efforts to reverse the current global environmental crisis increase, we are still experiencing unprecedented rates of species' extinctions. Traditional cultural landscapes can potentially play an important role for biodiversity conservation globally. However, these landscapes are threatened by pressures from global to local socio‐economic drivers of change. Many cultural landscapes across the world occur on private land where landowners' environmental stewardship can help support nature conservation. In this study, we applied a place‐based collaborative approach to understand the main aspects underlying landowners' relationship with nature, their perceptions of the local social–ecological context and their vision of a desired future to identify the constraints and opportunities to support voluntary private land conservation. The study was conducted in Uruguay, in a traditional cattle ranching cultural landscape, which is a national priority area for the conservation of biodiversity. In Uruguay, approximately 96% of the land is privately owned, while the National System of Protected Areas covers only 1% of the land. Our results revealed that landowners had a close relationship with nature and considered themselves and their neighbours as local environmental stewards. Landowners were well aware of the importance of nature contributions to their livelihood and lifestyle and were concerned that rural exodus to urban areas and shrubland encroachment would negatively impact the social–ecological context they value and depend upon. Main needs of landowners to support biodiversity conservation were not primarily motivated by economic interests, but more related to the need for support that could enhance land management and social cohesion. Biodiversity conservation goals in this cultural landscape cannot be pursued in isolation from social and rural development goals. Addressing local needs based on already existing links between nature's contributions and people might help support biodiversity conservation in the area. Failing to understand the context and to recognize locally perceived problems could increase the risk of voluntary conservation failure. Our approach and lessons learned can provide insights to actionable research in other cultural landscapes globally. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. Resumen: Mientras que los esfuerzos para revertir la actual crisis ambiental global aumentan, aún experimentamos tasas de extinción de especies sin precedentes. Los paisajes culturales tradicionales pueden jugar un rol importante para la conservación de la biodiversidad a escala global. Sin embargo, estos paisajes se encuentran amenazados por presiones asociadas a factores de cambio socio‐económicos, tanto locales como globales. Muchos paisajes culturales alrededor del mundo ocurren en tierras privadas, donde la custodia ambiental de los propietarios puede contribuir a la conservación de la naturaleza. En este estudio, implementamos una aproximación colaborativa con enfoque local para comprender los principales aspectos vinculados a la relación de los propietarios con la naturaleza, sus percepciones sobre el contexto socio‐ecológico local y su visión de un futuro deseado, como forma de identificar barreras y oportunidades para la conservación de la biodiversidad voluntaria en tierras privadas. El estudio fue realizado en Uruguay, en un paisaje cultural tradicional de ganadería pastoril, considerado un área prioritaria para la conservación de la biodiversidad a nivel nacional e internacional. En Uruguay, aproximadamente el 96% de la tierra se encuentra en propiedad de privados mientras que el Sistema Nacional de Áreas Protegidas cubre tan solo un 1% del territorio. Nuestros resultados evidenciaron que los propietarios tuvieron una relación cercana con la naturaleza y se consideraron a sí mismos y a sus vecinos como custodios ambientales. Los propietarios fueron conscientes de la importancia de las contribuciones de la naturaleza a su sustento económico y a su estilo de vida. A su vez, expresaron sus preocupaciones sobre los impactos negativos que pueden generar en el contexto socio‐ecológico que valoran y del cual dependen, tanto el éxodo rural como el avance no controlado de arbustos. Sus principales necesidades para contribuir a la conservación de la biodiversidad no estuvieron principalmente motivadas por intereses económicos sino relacionadas a la necesidad de recibir apoyos para mejorar el manejo de los campos y la cohesión social en la zona. Las metas de conservación de la biodiversidad en este paisaje cultural no pueden ser alcanzadas sin estar alineadas con metas sociales y de desarrollo rural. Dar cuenta de las necesidades locales, tomando como base los nexos ya existentes entre las contribuciones de la naturaleza y la gente, puede contribuir a apoyar la conservación en la zona. No comprender adecuadamente el contexto y no reconocer los problemas percibidos a nivel local puede aumentar el riesgo de fracaso de la conservación voluntaria. Nuestra aproximación y nuestras lecciones aprendidas pueden aportar insumos para la investigación aplicada en otros paisajes culturales a nivel global.